PENGGABUNGAN ONTOLOGI INSTRUMEN DAN GEONAMES - HERNAWATI SUSANTI SAMOSIR (JURNAL ILMIAH KOHESI, 2019)
In today's technological era, it cannot be denied that advanced knowledge and the way humans think can be written with a series of experiments on knowledge base engineering through protégé. At this time, a user has an interest in finding the regional origin of certain types of instruments. However, there are times when users enter different names for the same location. This study asks the ontology model to integrate two different domains, namely the licensed domain and location lending. The trick is to use owl: sameAs. From the result of test, it can be seen that the new ontology model can answer questions related to instrumens and locations. Whereas in this study the focus is on combining 2 ontology schemes, namely instruments and Geonames from East Nusa Tenggara and North Sumatera. Instrument ontology has parameters that will be related to geonames ontology that cosist of technique, material, place and geonames.